Modelagem e análise de condicionadores de ar dos tipos convencional e inteligente e influência no comportamento dinâmico das redes elétricas - Sanhueza, Sergio Manuel Rivera (2007)
Due to crescent demand and diversity of consumption equipments, the electrical power systems have presently shown operation problems, as in steady state to keep the voltage level within an appropriate range, as well as in transient state when facing disturbances such as short-circuit, generation loss, etc. For studying the effects of such disturbances in the planning stage of electric systems, accurate load models are very important to obtain reliable results. In the electric power utilities it is very common the adoption of the well-known ZIP model (constant impedance, current or power), however, when grid loads are composed by motors, such static model cannot be valid. This has motivated the search of a more detailed representation of several loads, mainly those considered more important or that are a larger proportion of the electric grid. In this context, the air conditioners deserve prominence, not only because of their high demand, but also for their dynamic peculiarities which influence the behaviour of the electric systems. Thus, this work has the objective of filling out some gaps as for the use and improvement of time domain models of air conditioner appliances, not only those simply controlled by thermostat the conventional air conditioners, but also the most advanced ones that possess temperature control by varying the motor speed the intelligent air conditioners. Besides, some simulations are accomplished to evaluate the dynamical behaviour of these two types of equipments after disturbances in the electric distribution grid and also to determine which type of air conditioner causes the largest influence.